HUBUNGAN DUKUNGAN SUAMI DENGAN KECEMASAN IBU HAMIL DALAM MENGHADAPI PERSALINAN DIPUSKESMAS RANDUAGUNG - Mayasari, Sepfriena Diah; Ekasari, Tutik; Rohmatin, Homsiatur (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Pregnancy is a period when the mother experiences physical hanges and psychological changes due to an increase in pregnancy hormones. Hormonal changes in pregnant womencause unstable or fluctuating emotions during pregnancy, so pregnant women feel sad, irritable, angry, and even feel happy. Objective: to determine the correlation between husband's support and anxiety in the third trimester of pregnant women. Population: all TM III pregnant women at the Randuagung Health Center totaling 36 pregnant women. Sample: Third-trimester pregnant women in the Randuagung Health Center Work Area, Lumajang in May as many as 36 people. Sampling using accidental sampling. This study used cross-sectional and this study uses the Rank Spearman correlation test. Results:The results of the Spearman analysis test showed p value = 0.004 so that p <0.05, which means that there is a relationship between the husband's support and trimester pregnant women's anxiety. high, the anxiety is mild, while if the husband's support is moderate, the anxiety is moderate. For health workers to provide information and collaborate with husbands or families in providing support to third-trimester pregnant women.